Analisa Usaha Budidaya Ikan Koi (Cyprinus rubrofuscus) pada Sistem Vertiqua Menggunakan Filter Biofikal Atas - M. Nurdin Nursamsi; Arif Supendi; Ujang Dindin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The background of this research is that vertiqua is considered to have high production costs and small profits. Therefore, a business analysis is needed to increase the effectiveness of the fish farming business using the vertiqua system. The purpose of this study is to analyze the aquaculture business using the vertiqua system including capital and profit obtained. This research uses qualitative methods with descriptive explanations. The results of the research that has been done show that the R / C Ratio value obtained is 1.66, meaning that every 1 cycle cost expenditure will get 1.66 revenue. Koi fish farming using the vertiqua system is said to be feasible to continue because the R / C Ratio value is 1. The JWPM value with the calculation of 8 cycles for 1 year is 1.4, meaning that it takes 2 months and 2 days for the capital to return. Based on the business analysis conducted, the production of koi fish seeds using the upper biofical filter vertiqua system can be said to be feasible and has the potential to be further developed, because it can provide good profits with a good JWPM. In addition, cultivation using the upper biofical filter vertiqua system is very efficient in providing care for koi fish cultivation.